ARSENIC SEGREGATION TO SILICON SILICON-OXIDE INTERFACES - Wong, C; Grovenor, C; Batson, P; Isaac, R (1985)
Arsenic segregation at polycrystalline silicon/silicon and polycrystalline silicon/silicon oxide interfaces was examined directly by transmission electron microscopy (TEM) and scanning transmission electron microscopy(STEM). Segregation occurring precisely at these interfaces was identified. A simple model was proposed based on arsenic segregation to structural units containing dangling bonds and consequent bond saturation. The removal of these dangling bonds will then play an important role in the electrical properties of these interfaces. Furthermore substitutional arsenic segregation at a degenerate level at these interfaces was also proposed. The subsequent dopant ionization and localized charges at the interfaces was discussed.